N-Heterocyclic Carbene Catalysis for Facile Access to Pentasubstituted 4H-Pyran Derivatives - Peng, Xiaolin; Wang, Yulin; Huang, Yixian; Zhang, Sheng; Jin, Zhichao; Ren, Shi-Chao (Synlett, 2024)
The synthesis of polysubstituted 4H-pyran derivatives has attracted considerable attention due to its wide application in agrochemicals, pharmaceuticals, and other functional molecules. We report an N-heterocyclic carbene-catalyzed [3+3] annulation reaction of β-ketone esters with enynals for rapid access to pentasubstituted 4H-pyran derivatives through a regioselective activation of the ynal. A series of 4H-pyran derivatives bearing various substituents were obtained in moderate to excellent yields. This method could find further applications in the synthesis of structurally diverse 4H-pyran-derived functional molecules from readily available starting materials.
Keywords: N-heterocyclic carbene catalysis; organocatalysis; pyrans; regioselectivity; ketone esters; enynals